Visualising personas as goal models to find security tensions - Shamal Faily (5515142) (2021)
Purpose This paper aims to present a tool-supported approach for visualising personas as social goal models, which can subsequently be used to identify security tensions. Design/methodology/approach The authors devised an approach to partially automate the construction of social goal models from personas. The authors provide two examples of how this approach can identify previously hidden implicit vulnerabilities and validate ethical hazards faced by penetration testers and their safeguards. Findings Visualising personas as goal models makes it easier for stakeholders to see implications of their goals being satisfied or denied and designers to incorporate the creation and analysis of such models into the broader requirements engineering (RE) tool-chain. Originality/value The approach can be used with minimal changes to existing user experience and goal modelling approaches and security RE tools. Other Information Published in: Information & Computer Security License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1108/ics-03-2021-0035